Evaluasi Program Pelatihan Kompetensi Penyuluh Pertanian Lapangan (PPL) Tingkat Kecamatan (Kasus Kecamatan Kerambitan, Marga, dan Selemadeg Barat Kabupaten Tabanan, Provinsi Bali) - KOMBA, MINIUS; ASTITI, NI WAYAN SRI; PUTRA, I GEDE SETIAWAN ADI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.2, April 2019, 2019)
The Evaluation of the Training Program in Competencies of the Agricultural Field Elucidators in the District Level (the Cases Taking Place at Kerambitan District, Marga, and West Selemadeg District, Tabanan Regency, Bali Province) The development of the ability of an Agricultural Field Elucidator ‘Penyuluh Pertanian Lapangan (PPL)’ plays a highly important role in the transformation of the accurate and efficient agricultural technological innovation. This current study was intended to identify the level of the knowledge and ability which the PPLs have after joining the training program which was held to improve their competencies, and to identify the obstructions faced when joining the program. The respondents totaled 30 determined using the saturated sampling technique. The data were analyzed using the descriptive qualitative method. The results of the study showed that after joining the training program, the competencies they had were good enough or fine and the score achieved was 3.00. The obstructions they faced were limited funds, time, labor and facilities. Apart from that, the perception which BPTP had was different from that which PPL and the other related parties had; as a result, the program was not in accordance with what had been expected for.Based on the result of the evaluation, it is suggested that the related parties should pay more attention to the funds, time and facilities used. In addition, the coordination between BPTP and PPL and the other related parties should be improved to make the result achieved from the program in accordance with what had been expected.